2011
DOI: 10.1111/j.1464-5491.2011.03284.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of myoinositol supplementation on insulin resistance in patients with gestational diabetes

Abstract: Myoinositol improves insulin resistance in patients with gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 20 publications
2
103
0
8
Order By: Relevance
“…Araştırma sonunda MI+FA alan grupta açlık kan glukozu, insülin düzeyi ve insülin direncinin diğer gruba göre daha düşük olduğu bulunmuştur. 28 Emine ELİBOL ve ark.…”
Section: Gestasyonel Di̇abetes Melli̇tusunclassified
“…Araştırma sonunda MI+FA alan grupta açlık kan glukozu, insülin düzeyi ve insülin direncinin diğer gruba göre daha düşük olduğu bulunmuştur. 28 Emine ELİBOL ve ark.…”
Section: Gestasyonel Di̇abetes Melli̇tusunclassified
“…A legújabb hipotézis szerint a mioinozitol képes javítani az inzulinrezisztenciát. Metabolikus hatása is kedvező, mert csökkenti az LDL-koleszterin-és trigliceridszintet, illetve a HDL-koleszterin-szintet növeli [8]. Az utóbbi egy-két évben több prospektív tanulmány leírta, hogy a GDM gyakorisága csökken PCOS-es, illetve cukorbetegség irányában pozitív családi anamnézisű várandósok esetében, ha a gondozás alatt mio-inozitol étrend-kiegészítésben részesültek [19,20].…”
Section: Táblázatunclassified
“…Ha a napi szükséglet szintje nő (például: PCOS, GDM), vagy a sejtekben alacsony a koncentrációja, az hozzájá-rulhat az inzulinrezisztencia létrejöttéhez [1][2][3][4][5][6][7]. Ezekben az esetekben a mio-inozitol pótlása javíthatja az inzulinérzékenységet [8].…”
unclassified
“…In particular, Corrado et al found a decreased fasting glucose and insulin in GDM patients treated by 4 g MI daily [16]. Afterwards, D'Anna et al have published the first report about the effect of MI on GDM occurrence in PCOS infertile women [17].…”
Section: Inositol As a Therapeutic Option To Prevent Gdmmentioning
confidence: 99%
“…Considering the insulin-mimetic effect of inositol supplementation in several animal models of insulin resistance [12][13][14] and in women with polycystic ovary syndrome (PCOS) [15], it has been recently hypothesized and studied its positive on the GDM incidence [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%